Previous Marriage Outcomes and Fertility Preference among Re-Married Women in Nigeria: Analysis from 2013 Nigeria Demographic and Health Survey - Olaseinde, Olugbenga (International Journal of Business Strategy and Social Sciences, 2020)
With increasing rate of re-marriage, women’s decision to stick to their intended fertility may be influenced by the dictate of men who demand additional child to consummate the new union. This study examined the influence of previous marriage outcome on women’s fertility preference by analysing 2013 NDHS weighted sample data of 2,671 Nigerian women, who reported to have re-married. The analysis employed Chi-square test and Multinomial Logistic Regression Model. The result indicates that, apart from previous marriage outcome, ideal number of children, wealth status, and ethnicity are predictors of re-married women’s fertility preference. Women who lost their husband in their previous marriage were more likely to desire no more children than other categories of women. The study recommends enlightenment campaign to empower women, especially the widowed to make informed choices about their marital status after the death of husbands, also, to increase their sexual bargaining power in later remarried union.